(untitled) (Malaysian Journal of Civil Engineering, 2017)
Great difficulty can be met in justifying of many high and steep slopes in residual soils, even under heavy rainfall, and yet some slopes fail during heavy rainfall and some after remaning stable for many years. It is now clear that unsaturated zone plays a crucial role in the slope stability as it is the link between surface and groundwater. The objective of this paper is to develop a solution where the unsaturated flow equation and the formulation of appropriate effective stress equation and parameters for such soils can be solved simultaneously